Rain water collecting device with filtering capability - LI YAZHE (2018)
The utility model discloses a rain water collecting device with filtering capability, collect funnel, box, solar cell panel, electric power storage box, ozone generator and base including the rainwater, the top both sides of box are all fixed and are equipped with rainwater collection funnel, the fixed support that is equipped with between the funnel is collected to the rainwater, the fixed solarcell panel that is equipped with in top of support, the support internal fixation is equipped with the electric power storage box, solar cell panel links to each other with electric power storage boxelectrical property, top in the box is equipped with the filter sterilization case, the filter sterilization incasement is equipped with cotton filter layer of PP and active carbon filter layer, the cotton filter layer of PP is located active carbon filter layer top, filter sterilization case middle part is fixed, and be equipped with the interlayer and the interlayer bottom is equipped with ozonegenerator. This kind of re